Post-COVID-19 syndrome and quality of life impairment in severe COVID-19 Mexican patients - Román-Montes, Carla Marina; Flores-Soto, Yesenia; Guaracha-Basañez, Guillermo Arturo; Tamez-Torres, Karla María; Sifuentes-Osornio, José; González-Lara, Ma. Fernanda; León, Alfredo Ponce de (Frontiers in Public Health, 2023)
Introduction Post-COVID-19 syndrome (PCS) usually occurs 3 months after the onset of COVID-19 with a symptom duration of at least 2 months without an alternative diagnosis. Objective This study aimed to describe the prevalence, characteristics, and impact on the quality of life (QoL) of post-COVID-19 syndrome in patients with a history of hospitalization for COVID-19. Materials and methods We conducted a cross-sectional study. Patients who required hospitalization due to COVID-19 between March 2020 and October 2021 were invited to answer a PCS questionnaire and the EQ-5D instrument. A total of 246 patients were included: 187 (76%) met the definition of PCS and 54% were men, with a median age of 50 years (IQR 41–63). Results From 187 patients with PCS, the median time to symptom onset after hospital discharge was 1 day (IQR 1–20), and the median symptom duration was 150 days (IQR 90–225). A total of 27 different symptoms were reported; the most frequent were difficulty concentrating (81%), dyspnea (75%), arthralgia (71%), fatigue (68%), and hair loss (60%). Some symptoms, such as difficulty concentrating, arthralgia/myalgia, and hair loss, were more prevalent in women with PCS. Patients with PCS had a higher frequency of tobacco smoking (37 vs. 4%, p = 0.02) and increased severity of lung involvement in the initial chest tomography (75 vs. 58%, p = 0.01) than those without PCS. Patients with PCS were less likely to receive antivirals (15.5 vs. 27%, p = 0.04). No difference between ICU admission, mechanical ventilation, and length of hospital stay was found. Patients with PCS had a lower visual analog scale result for EQ-5D vs. those without (80 [IQR 70–90] vs. 89.5 [IQR 75–90], p = 0.05). All five QoL dimensions were affected in PCS patients, showing increased pain/discomfort (67 vs. 39%, p = < 0.001), difficulties in performing usual activities (39.2 vs. 20.3%, p = 0.03), and anxiety/depression (57.5 vs. 37%, p = 0.02). Conclusion PCS occurred in 76% of hospitalized patients with prolonged duration and QoL impairment. Neurological symptoms such as difficulty concentrating were the most frequent symptoms. Timely diagnostic and therapeutic interventions are required.